PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) IPA MENGGUNAKAN PENDEKATAN SAINTIFIK MATERI ZAT ADITIF PADA MAKANAN DI SMP N 8 SATAP TONDANO - Kiranda Briandy Buyung; Ni Wayan Suriani; Jovialine A Rungkat (SOSCIED, 2023)
The Purpose in this study aims to develop Student Worksheets (LKPD) at SMP N 8 SATAP Tondano and to determine the feasibility of LKPD at SMP N 8 SATAP Tondano. This type of research uses Research and Development (R&D) research and development methods. The research model used is the ADDIE Analysis, Design, Development, Implementation, Evaluation model. The research instrument used a questionnaire consisting of a material expert questionnaire, a media expert questionnaire and a questionnaire for product trials (small groups). Based on the material expert validation trial in the form of a questionnaire obtained a result of 98% based on the results of the media expert validation trial obtained a result of 92%. The percentage is in very good category and is suitable for use in the field. Then the small group tryout consisting of 12 students at SMP N 8 SATAP Tondano obtained 86% results, so that the IPA LKPD especially on the subject of food additives developed was included in the "Very Good" criteria.